Protective Efficacy of an AIDS Vaccine, a Single DNA Priming Followed by a Single Booster with a Recombinant Replication-Defective Sendai Virus Vector, in a Macaque AIDS Model - Takeda, Akiko (American Society for Microbiology, 2003)
We previously demonstrated the excellent protective efficacy of DNA priming followed by Gag-expressing Sendai virus (SeV) boosting (DNA prime/SeV-Gag boost vaccine) against a pathogenic simian-human immunodeficiency virus (SHIV89.6PD) infection in macaques. Here we show that we established a practical, safer AIDS vaccine protocol, a single DNA priming followed by a single booster with a recently developed replication-defective F deletion SeV-expressing Gag, and show its protective efficacy against SHIV89.6PD infections.